Clinical Presentation, Investigation and Control of an Outbreak of Adenoviral Conjunctivitis in a Neonatal Unit at a Tertiary Hospital. Issue 3 (March 2022) - Thakur, Anchal; Goyal, Kapil; Chauhan, Poonam; Sharma, Bhawna; Kant Dhir, Shashi; Katoch, Deeksha; Biswal, Manisha; Talati, Shweta; Bhogal, Ranjitpal Singh; Mohan, Lalit; Sapra, Monika; Gupta, Amit; et al.
Abstract : Background: Nosocomial spread of adenovirus infection has been reported in neonatal, pediatric and adult medical units. This nonenveloped and hardy virus is resistant to numerous disinfectants thus posing a challenge for control and prevention of adenovirus infections in health care settings. Methods: An epidemiologic outbreak investigation revealed an adenoviral outbreak in the neonatal nursery as well as in the neonatal screening outpatient department for Retinopathy of Prematurity (ROP). All suspected cases (94 neonates) underwent adenoviral conventional polymerase chain reaction (PCR) and representative samples underwent sequencing by Sanger's method. The clinical features and disease course were studied. Infected babies were started on tobramycin eye drops. Topical steroid eye drops were added for those who developed pseudomembranes. Results: We found 58 cases of laboratory-confirmed neonatal adenovirus conjunctivitis (between July 10 and October 24, 2019). Redness (96%) was the most common presentation followed by discharge (68.9%) and lid edema (51.7%). Pseudomembrane were seen in 77.5% of the infected neonates. Prior ROP examination was carried out in 38 (65.5%) neonates. Respiratory symptoms were present in 7 (12.06%) neonates. Sequencing revealed serotype 8 as the cause of the outbreak. Control measures were strictly implemented. Standard Operating Procedures (SOPs) for ROP screening were revisited, revised and reinforced to prevent future outbreaks. Conclusions: We observed ROP screening as a risk factor for the development of adenoviral conjunctivitis in neonatal care units. Neonates present with different clinical manifestations as compared with adults. Prompt control measures were implemented to control the adenoviral outbreak.